Genes and pathways monotonically dysregulated during progression from normal through leukoplakia to gingivo-buccal oral cancer - Debodipta Das (Nature Portfolio, 2021)
Abstract Oral squamous cell carcinoma of the gingivo-buccal region (OSCC-GB) accounts for the highest cancer morbidity and mortality among men in India. It has been observed that about one-third of individuals with oral leukoplakia, a dysplastic precancerous lesion in the oral cavity, progress to oral cancer. We aimed to identify systematic transcriptomic changes as a normal tissue in the oral cavity progresses to frank OSCC-GB. Seventy-two OSCC-GB patients, from multiple hospitals, were recruited, and transcriptome analysis of tumor and adjacent normal tissue (of all patients) and adjacent leukoplakia tissue (of a subset of 25 unselected patients with concomitant leukoplakia) was performed. We have identified many differences in the transcriptomic profiles between OSCC-GB and squamous cell carcinoma of the head and neck regions. Compared to the normal/precancerous tissue, significant enrichment of ECM−receptor interaction, PI3K-Akt signaling, cytokine−cytokine receptor interaction, focal adhesion, and cell cycle pathways were observed in OSCC-GB. Using gene set enrichment analysis, we identified a profound role of interferon receptor signaling in tumor growth by activating immune evasion mechanisms. The role of tumor-infiltrating immune cells further supported the growth and immunosuppressive mechanism of tumor tissues. Some immune evasion genes—CD274, CD80, and IDO1—were found to be activated even in the precancerous tissue. Taken together, our findings provide a clear insight into the sequential genetic dysregulation associated with progression to oral cancer. This insight provides a window to the development of predictive biomarkers and therapeutic targets for gingivo-buccal oral cancer.